2017
DOI: 10.1111/pace.13238
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in low upright baroreflex sensitivity is associated with positive clinical effect of orthostatic training

Abstract: OT reduced symptoms in 74% patients who trained regularly. However, the compliance to training was low. Possible mechanism of OT is reconditioning effect on baroreceptor reactivity in upright position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Others have also reported similar figures in normal subjects (83). The BRS has been found to be low even in resting conditions in those with poor orthostatic tolerance and the index does not change much on exposure to orthostatic stress (69,84). In fact it has been suggested that the defect may lie at the sensory receptor level where the changes in the pulsatile pressure are not sensed adequately (69).…”
Section: Baro Reflex Sensitivity (Brs) and Syncopementioning
confidence: 76%
See 1 more Smart Citation
“…Others have also reported similar figures in normal subjects (83). The BRS has been found to be low even in resting conditions in those with poor orthostatic tolerance and the index does not change much on exposure to orthostatic stress (69,84). In fact it has been suggested that the defect may lie at the sensory receptor level where the changes in the pulsatile pressure are not sensed adequately (69).…”
Section: Baro Reflex Sensitivity (Brs) and Syncopementioning
confidence: 76%
“…There have been attempts to improve responses of patients with recurrent VVS by orthostatic training (84). Patients of VVS were asked to lean against a wall with their feet placed 15 cm away from the wall.…”
Section: Principles Of Management Of Vvsmentioning
confidence: 99%
“…Detection of BRS is not only beneficial to patients who would potentially receive beta-blocker treatment but also to those receiving orthostatic training. Orthostatic training is considered to cure patients with VVS accompanied by sympathetic nervous dysfunction, another subset of patients with autonomic nervous activity alterations (Tan et al, 2010;Mitro et al, 2018). Both Tan et al and Mitro et al found that BRS was increased after the intervention of orthostatic training, and furthermore, Mitro et al identified that VVS patients with lower upright BRS had better outcomes than those with relatively higher values.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal changes in baroreceptors are one of the important pathogeneses of VVS. Measurements of baroreflex sensitivity (BRS) can evaluate the response to baroreceptors in the process of arterial pressure changes and reflect sympathetic nerve activity ( 6 ). The pre-treatment supine BRS of children with VVS to whom β-blockers are effective is much higher than that of children to whom β-blockers are ineffective.…”
Section: Individualized Beta-blocker Therapy For Children With Vvs: B...mentioning
confidence: 99%
“…Currently, known therapeutic methods of VVS include pharmacological and non-pharmacological therapies. Beta-blockers, α1-adrenergic receptor agonist, sertraline, fludrocortisone, and oral rehydration salts are commonly used pharmacological treatments for VVS ( 1 , 5 , 6 ). This review summarizes the latest advances of biomarkers that can predict the therapeutic efficacy of β-blocker in children with VVS, and points out the advantages and disadvantages of these biomarkers.…”
Section: Introductionmentioning
confidence: 99%